Integração de padrões de qualidade na área de melhoria de processo de software - Espindola, Rodrigo Santos de (2011)
Both industry and academy has been demonstrating a great interest for software process improvement (SPI) as an agent for improving software product quality. One of the strategies followed in seeking software process improvement is the adoption of quality standards (standards and reference models) to guide SPI projects. However, given the wide variety of quality standards available for SPI, organizations have been faced new challenges related to integration, comparison, mapping and harmonization of these standards. One difficulty found when trying to analyze the differences and similarities between the various quality standards is the lack of uniformity in their definitions. The quality standards have different vocabularies, different structures, different levels of abstraction and different requirements in terms of granularity. This means that they are adopting completely different representations. Thus, this thesis aims to answer the following research question: How to make the representation of quality standards for SPI so that it can support the standards integration? The overall objective is to propose an approach to represent quality standards for SPI so that it can support their integration. To achieve this, an exploratory study was conducted, using as research methods case study, survey, documents based research and design and creation method. As a result, this thesis proposes a conceptualization of quality standards domain for SPI, explained through the development of quality standards ontology for SPI, and a modeling language based on this ontology, explicit by the development of a quality standard metamodel for SPI.